OPTIMIZING THE DAILY UNITS OF INSULIN; INSULIN DEGLUDEC ASPART VERSUS PREMIXED INSULIN ASPART IN THE STANDARD OF CARE REGIMEN FOR TYPE 2 DIABETICS - Malik, Komal Mumtaz; Farhat, Kulsoom; Ali, Shabana; Noor, Mudassar; Ahmad, Bilal (Journal of Ayub Medical College Abbottabad, 2023)
B Background: This study aimed to evaluate the impact of Insulin Degludec Aspart on daily insulin dose in comparison with premixed insulin aspart. Methods: It was a Quasi-Experimental study conducted in the Department of Pharmacology, Army Medical College, National University of Medical Sciences, Rawalpindi and the Department of Medicine, Pak Emirates Military Hospital, Rawalpindi. One hundred and twenty participants with documented type 2 diabetes, taking premixed insulin aspart therapy were enrolled in the study. Sixty participants were substituted with insulin degludec aspart from premixed insulin aspart. Daily units of insulin were recorded for 12 weeks and compared for both groups. SPSS version 26 was used for analysing the study results. Results: Participants of the insulin degludec aspart group showed a significant reduction in the daily insulin dose compared to the premixed insulin aspart group. Fifty-two units per day were administered in the participants of the premixed insulin aspart patients while insulin degludec aspart participants received 40 units of median daily insulin dose (p-value<0.001). Conclusion: Insulin degludec aspart proved superior to premixed insulin aspart in a reduction in the daily dose of insulin with insulin degludec aspart